EVALUATION RESPONSE OF EIGHT POTATO CULTIVARS IN VITRO GROWTH UNDER SALT STRESS CONDITIONS TO - & Jawad, Khierallah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The objective of this study evalution response of eight of potato cultivars growth to salt stress. Eight potato imported varieties were chosen: Almondo, Arizona, Buren, Everest, Riviera, Rudolph,Sever and Sylvana. In vitro cultures of these varieties were established in order to study the effect of various concentrations (0, 50, 100, 150 and 200 mM of NaCl) on some in vitro growth parameters of shoots. Results showed that the Riviera variety was tolerate to NaCl salt stress condition at the saline concentrations used for vegetative growth parameters followed by Arizona and Buren. As for the chlorophyll content at the saline concentrations, no chlorophyll content was produced in 150 and 200 mM. There were significant differences in the content of proline with the increasing saline stress and increased the starch content in the vegetative parts at 100 mM NaCl and a decrease in the percentage of carbohydrates was observed by increasing saline concentrations. Dendogram of the genetic relationship using the UPGMA method and based on the Euclidean algorithm of phenotypic characteristics showed that the potato varieties were divided into two main groups and with 5.8 genetic distance. The above results can be employed in potato breeding and improvement for salts tolerance programs.